Students’ Assessment of Mathematics Teachers’ Teaching Styles in Private and Public Schools in Kathmandu Valley - Khanal, Bishnu (Rainbow Journal, 2019)
This paper attempts to investigate the students’ assessment of teaching styles of their mathematics teachers. The study examines how do the students assess the teachers’ teaching styles and what effect does it have in the mathematics achievement of students by public and private schools in Kathmandu valley. Sequential explanatory mixed method was adopted in the study as research method. The descriptive cross-sectional survey study used the questionnaire and FGD as the tools to collect data from the population sampled purposively. The study was carried out in 14 schools which were selected purposively and 469 students from these schools were selected using census sampling as respondents in the study. The findings chows that there is no significant difference between, public and private school students, in their assessment of teachers’ teaching styles. This result was substantiated by qualitative data analysis that the assessment of teaching styles by public and private school students were not found different. Students from both public and private school preferred inductive method and respect and encouragement with practical methods in teaching mathematics. The output of the study can enhance the developing and improving teaching style of teachers in classroom practices.